The Crk adapter protein is essential for Drosophila embryogenesis, where it regulates multiple actin-dependent morphogenic events. - Spracklen, A.J.; Thornton-Kolbe, E.M.; Bonner, A.N.; Florea, A.; Compton, P.J.; Fernandez-Gonzalez, R.; Peifer, M. (Molecular Biology of the Cell, 2019)
Small Src homology domain 2 (SH2) and 3 (SH3) adapter proteins regulate cell fate and behavior by mediating interactions between cell surface receptors and downstream signaling effectors in many signal transduction pathways. The CT10 regulator of kinase (Crk) family has tissue-specific roles in phagocytosis, cell migration, and neuronal development and mediates oncogenic signaling in pathways like that of Abelson kinase. However, redundancy among the two mammalian family members and the position of the Drosophila gene on the fourth chromosome precluded assessment of Crk's full role in embryogenesis. We circumvented these limitations with short hairpin RNA and CRISPR technology to assess Crk's function in Drosophila morphogenesis. We found that Crk is essential beginning in the first few hours of development, where it ensures accurate mitosis by regulating orchestrated dynamics of the actin cytoskeleton to keep mitotic spindles in syncytial embryos from colliding. In this role, it positively regulates cortical localization of the actin-related protein 2/3 complex (Arp2/3), its regulator suppressor of cAMP receptor (SCAR), and filamentous actin to actin caps and pseudocleavage furrows. Crk loss leads to the loss of nuclei and formation of multinucleate cells. We also found roles for Crk in embryonic wound healing and in axon patterning in the nervous system, where it localizes to the axons and midline glia. Thus, Crk regulates diverse events in embryogenesis that require orchestrated cytoskeletal dynamics.